Diagnostic dilemma: think about anterior cutaneous nerve entrapment syndrome (ACNES) in patients with atypical abdominal pain and Crohn's disease. (28th March 2018) - Lam, Kenneth; Vasey, Carolyn
Abstract : Chronic abdominal pain can be a difficult diagnostic dilemma. Anterior cutaneous nerve entrapment syndrome (ACNES) is a potential differential diagnosis that should be considered because treatment is both easy and effective. We describe the case of a 51-year-old man presenting with 7 months of right lower quadrant abdominal pain on the background of known Crohn's disease. A circumspect surgical approach and multidisciplinary input was key to making the diagnosis of a nerve entrapment syndrome.